Investigation on Chlamydia trachomatis infection in Sanya from 2012 to 2016 - Qiong-jun Xu (Asian Pacific Journal of Tropical Medicine, 2018)
Objective: To understand the epidemiology of Chlamydia trachomatis (C. trachomatis) infection in genital tract in Sanya, and to provide scientific basis for adjusting the existing prevention and control measures. Methods: The cases of C. trachomatis infection in genital tract reported by medical institutions in Sanya from 2012 to 2016 were collected through the disease information management system for descriptive epidemiological analysis. Results: The average annual incidence of C. trachomatis infection in genital tract of Sanya from 2012 to 2016 was 273.02 per 100 000, with an average annual growth rate of 8.40%, and the incidence of C. trachomatis infection in genital tract has been increasing for 5 years (χ2=55.591, P< 0.001). The cumulative number of reported cases of C. trachomatis infection in genital tract in males was 2 617, and that in females was 5 287, the ratio between men and women was 0.49:1. The difference in the incidence rate between men and women was statistically significant(P < 0.05). The cumulative number of reported cases in Tianya District was the highest (7 662 cases), followed by Haitang District (242 cases), and no cases were reported in township hospitals and community health service centers. In the age distribution, the incidence of C. trachomatis infection in genital tract was the highest in the group aged 20-29 years, which was 155.30/100 000, and lowest in the group aged over 60 years, which was 0.97/100 000. The occupation was mainly engaged in houseworkers or unemployed and commercial services. Conclusions: At present, the incidence of C. trachomatis infection in genital tract of Sanya is at a high level. It is necessary to expand screening, strengthen education, and attention should be paid to reduce cross-infection and monitoring drug-resistant strains.